1995
DOI: 10.1111/j.1532-5415.1995.tb07397.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Year Trends in Cardiorespiratory Function Among Older Tai Chi Chuan Practitioners and Sedentary Subjects

Abstract: The data substantiate that practicing Tai Chi Chuan regularly may delay the decline of cardiorespiratory function in older individuals. In addition, TCC may be prescribed as a suitable aerobic exercise for older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(96 citation statements)
references
References 18 publications
(22 reference statements)
6
89
0
1
Order By: Relevance
“…In this way, several studies thathave been conductedshow improvements in cardiorespiratory function and cardiovascular risk reduction, as well asin lexibility and balance (9,10). Regarding cardiovascular risk, according to the guidelines of ACSM and AHA, the practice of aerobic and resistance exercises are recommended to either healthy (2) and cardio paths, due to the phenomenon known as Post Exercise hypotension (PHE) (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, several studies thathave been conductedshow improvements in cardiorespiratory function and cardiovascular risk reduction, as well asin lexibility and balance (9,10). Regarding cardiovascular risk, according to the guidelines of ACSM and AHA, the practice of aerobic and resistance exercises are recommended to either healthy (2) and cardio paths, due to the phenomenon known as Post Exercise hypotension (PHE) (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Non-randomised controlled studies have suggested that Tai Chi may enhance cardiorespiratory functioning in healthy older people [35,37,52] although there have been mixed findings [2]. Authors in the 1990s proposed that Tai Chi may delay the decline of cardiorespiratory function in older adults [52], and that older TCC practitioners had better cardiorespiratory fitness, muscular strength and flexibility than their sedentary counterparts [35].…”
Section: Physical Fitness and Aerobic Capacitymentioning
confidence: 99%
“…Authors in the 1990s proposed that Tai Chi may delay the decline of cardiorespiratory function in older adults [52], and that older TCC practitioners had better cardiorespiratory fitness, muscular strength and flexibility than their sedentary counterparts [35]. A2008 meta-analysis [54] concluded that Tai Chi exercise is effective in improving aerobic capacity (ES = 1.33) when practiced long term.…”
Section: Physical Fitness and Aerobic Capacitymentioning
confidence: 99%
“…[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] Of these, 13 eval- uated yoga, 20 tai chi, 9 qi gong, and 1 tai chi and qi gong combined. Yoga, tai chi, and qi gong are discussed together in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies focused on patients with respiratory disorders: COPD, 38,41,43,45,51,52,72,75 asthma 42,47 and pleural effusion. 48 Twenty-seven studied healthy people: older adults, 34,35,50,55,57,58,[60][61][62][63][64][65][73][74][75][76][77] healthy adults, 59 healthy males, 66,69 soldiers, 44 students, 46,53,71 children, 37 "residents," 59 and practitioners of tai chi/yoga. 56,67,68 The remaining 6 studies were on non-respiratory disorders (lower-limb disabilities, 70 breast cancer patients, 54 heart disease, 49 impaired vision, 36 Parkinson's disease, 40 and hypertension 39 ) but also measured respiratory outcomes.…”
Section: Samplesmentioning
confidence: 99%